Item response theory for psychologists - Embretson, Susan E. (Lawrence Erlbaum Associates, 2000)
The purpose of this book is to explain item response theory (IRT) to a primarily psychological audience that is familiar with small-scale cognitive and personality measures or that wants to use IRT to analyze scales used in their own research. Herein, familiar psychological concepts, issues, and examples are used to help explain various principles in IRT. The authors first seek to develop the reader's intuitive understanding of IRT principles by using graphical displays and analogies to classical measurement theory. Then, the book surveys contemporary IRT models, estimation methods, and computer programs. Because many psychological tests use rating scales, polytmous IRT models are given central coverage. Applications to substantive research problems, as well as to applied testing issues, are described. The book is intended for psychology professionals and graduate students who are familiar with testing principles and classical test theory.